Anti-inflammatory, cytotoxicity and antilipidemic properties: novel bioactivities of true cinnamon (Cinnamomum zeylanicum Blume) leaf - Walimuni Prabhashini Kaushalya Mendis Abeysekera; Galbada Arachchige Sirimal Premakumara; Wanigasekera Daya Ratnasooriya; Walimuni Kanchana Subhashini Mendis Abeysekera (BMC, 2022)
Abstract Background The leaf of Ceylon cinnamon (true cinnamon) is traditionally claimed for a variety of health benefits. However, reported scientific information is scanty and needs urgent attention for value addition. Methods Ethanolic (95%) and Dichloromethane:Methanol (DM, 1:1 v/v) leaf extracts of Ceylon cinnamon were evaluated for a range of medically important bioactivities namely anti-inflammatory [nitric oxide scavenging activity (NOSA), superoxide scavenging activity (SCA), COX1 and COX2 inhibition], growth inhibition & cytotoxicity against MCF7, HePG2 and AN3CA carcinoma cell lines, glutathionase-S-transferase (GST) inhibition and antilipidemic (anti-HMG-CoA reductase, anti-lipase, anti-cholesterol esterase, and cholesterol micellization inhibition) properties in vitro (n = 3). Further, a range of bioactive compounds in both leaf extracts was also quantified (n = 3). Results Both leaf extracts had all the investigated bioactive compounds and possessed moderately potent bioactivities compared to the reference drugs used in the study. Ethanolic leaf extract (ELE) exhibited the highest activities (IC50: μg/mL) for NOSA (40.26 ± 0.52), SCA (696.24 ± 40.02), cholesterol esterase inhibition (110.19 ± 1.55), cholesterol micellization inhibition (616.69 ± 7.09), GST inhibition (403.78 ± 2.70) and growth inhibition (GI50: 144.84 ± 1.59-269.00 ± 0.51) & cytotoxicity (LC50: 355.44 ± 9.38-717.71 ± 23.69) against studied cancer cell lines. In contrast, COX1 & COX2 (IC50: 6.62 ± 0.85 and 44.91 ± 3.06 μg/mL) and HMG-CoA reductase & lipase inhibitory activities (36.72 ± 4.74 and 19.71 ± 0.97% inhibition at 200 and 600 μg/mL) were highest in DM extract. ELE also showed the highest quantities (0.81 ± 0.06-104.38 ± 1.79) of tested compounds (mg/g extract) where eugenol was the highest and gallic acid was the lowest among quantified. Conclusion Both leaf extracts of Ceylon cinnamon had all the tested bioactive compounds and possess all the investigated bioactivities. This is the 1st study to report all the investigated bioactivities of the leaf of Ceylon Cinnamon.